2019
DOI: 10.1164/rccm.201807-1333oc
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Risk Factors for Mortality in an Adult Community-acquired Pneumonia Cohort in Malawi

Abstract: Rationale: In the context of rapid antiretroviral therapy rollout and an increasing burden of noncommunicable diseases, there are few contemporary data describing the etiology and outcome of community-acquired pneumonia (CAP) in sub-Saharan Africa. Objectives: To describe the current etiology of CAP in Malawi and identify risk factors for mortality. Methods: We conducted a prospective observational study of adults hospitalized with CAP to a teaching ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 48 publications
(66 reference statements)
12
55
0
3
Order By: Relevance
“…Furthermore, a recent cohort study in Malawi of a similar population of adult patients with pneumonia revealed that, after tuberculosis, the most common etiology of pneumonia was Streptococcus pneumoniae , followed by respiratory viruses, in both HIV-infected and HIV-uninfected patients. [46] Therefore, the likelihood of substantial differences in pneumonia etiology between HIV-infected and HIV-uninfected participants is small and we do not think that this possibility invalidates our results.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, a recent cohort study in Malawi of a similar population of adult patients with pneumonia revealed that, after tuberculosis, the most common etiology of pneumonia was Streptococcus pneumoniae , followed by respiratory viruses, in both HIV-infected and HIV-uninfected patients. [46] Therefore, the likelihood of substantial differences in pneumonia etiology between HIV-infected and HIV-uninfected participants is small and we do not think that this possibility invalidates our results.…”
Section: Discussionmentioning
confidence: 73%
“…[10] However, the most common pathogens of adult community-acquired pneumonia in Malawi, a developing country in Africa were S. pneumoniae, Mycobacterium tuberculosis and non-Mycobacterium tuberculosis. [11] We found that in different regions of the world, the pathogenic bacteria of LRIs were signi cantly different. Therefore, it was of great signi cance to analyze the distribution of local pathogens for epidemiological research and clinical experience.…”
Section: Discussionmentioning
confidence: 79%
“…27 The next study of that scale was completed only recently in Malawi. 28 Clinically Relevant-Our group studies alveolar macrophage function in HIV in Malawi. While working on this, however, we also noted high levels of carbonaceous material.…”
Section: Research In Low-and Middle-income Countriesmentioning
confidence: 99%